Strategi Majelis Ulama Indonesia (Mui) Desa Dalam Meningkatkan Pemahaman Moderasi Beragama Studi Kasus di Desa Tegal Waru Kecamatan Ciampea Kabupaten Bogor: Pemahaman Moderasi Beragama - Abidin, Zaenal (STIT Sirojul Falah Bogor, 2023)
ABSTRACT Strategy of the Indonesian Ulema Council (MUI) in Increasing Understanding of Religious Moderation. Case Study at MUI Village, Ciampea District, Bogor Regency. Islamic education study program. Sirojul Falah Bogor Tarbiyah College. This study aims to determine how the strategy of the MUI in Ciampea Village in increasing understanding of religious moderation and the obstacles faced in carrying out its programs. This type of research uses a qualitative approach, with a case study method while the data analysis method is descriptive. The data sources used are primary data, and secondary data. Data analysis techniques were carried out by reducing data, presenting data, and taking data obtained from sources related to the local MUI program. The results obtained are that with the running of programs and activities carried out by MUI, it can pay attention to improving the quality of public understanding so that they understand more about religion and knowledge taught in Islam which are then conveyed by scholars and scholars to every community, especially minorities. Keywords: Strategy, MUI, Religious Moderation